Penerapan Metode Six Sigma Untuk Mengidentifikasi Kecacatan Produk Mabel Pada Proses Produksi UMKM Agung Citra Meubel - Melli Yani; Tuwandi Juniarto (Jurnal Teknik Ibnusina, 2026)
The furniture industry faces challenges in maintaining product quality to improve customer satisfaction and competitiveness. Agung Citra Meubel MSME still experiences defects in sofa products such as misaligned stitching, loose stitching, and scratches, which increase rework, costs, and processing time. This study aims to identify the defect level, determine the main causes of defects, and Analyze the performance of the production process in meeting quality standards. The method used is Six Sigma with the DMAIC (Define, Measure, Analyze, Improve, Control) approach. Data were obtained through observation, interviews, and documentation during the research period. The results show a defect rate of 0.88% with a DPMO value of 1,470.59 and a sigma level of 4.5. Pareto analysis indicates that dominant defects are misaligned stitching, loose stitching, and scratches, while fishbone analysis identifies causes from human, machine, method, material, and environmental factors. Process capability evaluation shows Cp of 0.37 and Cpk of 0.36, indicating the process is not yet optimal. Control is carried out using an R-chart to maintain process stability. The implementation of Six Sigma effectively reduces defect variation and improves product quality, which is important for enhancing operational efficiency and customer satisfaction overall.